Development and validation of an echocardiographic algorithm to predict long-term mitral and tricuspid regurgitation progression. (29th November 2021) - Strom, Jordan B; Zhao, Yuansong; Shen, Changyu; Wasfy, Jason H; Xu, Jiaman; Yucel, Evin; Tanguturi, Varsha; Hyland, Patrick M; Markson, Lawrence J; Kazi, Dhruv S; Cui, Jinghan; Hung, Judy; et al.
Abstract: Aims: Prediction of mitral (MR) and tricuspid (TR) regurgitation progression on transthoracic echocardiography (TTE) is needed to personalize valvular surveillance intervals and prognostication. Methods and results: Structured TTE report data at Beth Israel Deaconess Medical Center, 26 January 2000–31 December 2017, were used to determine time to progression (≥1+ increase in severity). TTE predictors of progression were used to create a progression score, externally validated at Massachusetts General Hospital, 1 January 2002–31 December 2019. In the derivation sample (MR, N = 34 933; TR, N = 27 526), only 5379 (15.4%) individuals with MR and 3630 (13.2%) with TR had progression during a median interquartile range) 9.0 (4.1–13.4) years of follow-up. Despite wide inter-individual variability in progression rates, a score based solely on demographics and TTE variables identified individuals with a five- to six-fold higher rate of MR/TR progression over 10 years (high- vs. low-score tertile, rate of progression; MR 20.1% vs. 3.3%; TR 21.2% vs. 4.4%). Compared to those in the lowest score tertile, those in the highest tertile of progression had a four-fold increased risk of mortality. On external validation, the score demonstrated similar performance to other algorithms commonly in use. Conclusion: Four-fifths of individuals had no progression of MR or TR over two decades. Despite wide interindividual variability in progression rates, a score, based solely on TTE parameters, identified individuals with a five- to six-fold higher rate of MR/TR progression. Compared to the lowest tertile, individuals in the highest score tertile had a four-fold increased risk of mortality. Prediction of long-term MR/TR progression is not only feasible but prognostically important. Graphical Abstract: